Agriculture carbon pricing in EU, carbon leakage and carbon adjustment mechanism impacts in southern cone beef exports - Cabrini, Silvina María; Benito Amaro, Ignacio; Olemberg, Demián Jeremías; Cagnin, Santiago; Pace Guerrero, Ignacio Raul; Cristeche, Estela Raquel (Asociación Argentina de Economía Agraria, 2024)
Ponencia y presentación en diapositivas